Perceptions and Knowledge on the Effectiveness of a Local Government in Iran - Alekajbaf, Hossein (2005)
This study seeks to examine the perceptions and knowledge of local residents on the effectiveness of local government in Iran within the context of the process of decentralization. The study was based on qualitative and quantitative approaches. On the first, the study relied on published materials, both scholarly works and government data. On the, quantitative method, the study was based on a case study conducted in the Tehran City Council area. Quantitative data were collected using a set of questionnaire that was established within the Tehran City Council area. A total of 462 responses were successfully collected from the respondents. In addition, interviews were also conducted with selected informants who comprised officials of the local authority in Tehran city. The main findings of the study can be summarized as follows. Firstly, the study had discussed the development of local government as well as the process of decentralization in Iran and in particular the evolution of local government in Tehran city. Secondly, the study also discussed the structure and function of Tehran City Council, including discussing selected weakness in their structure and functions in relations to the delivery of services to the residents. Thirdly, the study also showed the low1 or negative level of perceptions among the respondents on the effectiveness of the functions of local government. The study also showed the weak relationship between the respondent’s and the officials of local authority. Lastly, the study showed that there were several areas that can be enhanced in order to improve on the functions of local government in its effort to provide better services to its resident, namely the need to review rules and regulations regarding local government, training needs of personnel of local authority, and the need to provide more information for residents so that the latter are aware of the services that they can get from their local authority.